Regularities of formation of structure, texture and properties under the combined plastic deformation of the low-carbon and ultralow-carbon steels for cold press forming - Projdak, Yu.S.; Kutsova, V.Z.; Kotova, T.V.; Stetsenko, H.P.; Prutchykova, V.V. (Успехи физики металлов, 2019)
The current paper reports the new solutions intended to enhance the complex of mechanical properties and tendency to the press forming of the hot-rolled low-carbon and ultralow-carbon steels with subsequent cold deformation via upsetting and torsion under hydrostatic pressure (THP).